PARAREM DALAM TRADISI PERKAWINAN MASSAL DI DESA PENGOTAN KABUPATEN BANGLI - Tresna Putra, Dewa Gede Yoga; Zuryani, Nazrina; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
Marriage is one of the important phases that will be passed in the lifecycle of Hindus. However, this is different from the marriages that occurred in the Bangli Traditional Village of Pengotan. This study uses the theory of social action, the type of research uses a qualitative approach. The technique of determining informants is purposive sampling. Data collection techniques are carried out through observation, interviews and document study. The data obtained were analyzed by steps, namely data reduction, data display, and drawing conclusions. The results of this study indicate to the Pararem mass marriages in the Pengotan Village Bangli, Bangli sub-district. The Pararem of mass marriage in the Pengotan Traditional Village has a very significant positive impact on the community, such as maintaining ancestral Inheritance in the form of Mass Marriage, Tourism Sector Growth in Pengotan Village through Mass Marriage and to arrange a Moral Education of the Young Generation. Keywords: Pararem Marriage, Pararem Role, Pararem Impact